Clinician perspectives on strategies to improve patient maternal immunization acceptability in obstetrics and gynecology practice settings. Issue 7 (3rd July 2018) - Frew, Paula M.; Randall, Laura A.; Malik, Fauzia; Limaye, Rupali J.; Wilson, Andrew; O'Leary, Sean T.; Salmon, Daniel; Donnelly, Meghan; Ault, Kevin; Dudley, Matthew Z.; Fenimore, Vincent L.; Omer, Saad B.
ABSTRACT: Pregnancy is an ideal time to communicate with women about vaccines for themselves and their infants, yet maternal immunization rates remain suboptimal. This study aimed to identify clinic, provider, and staff-related attributes and facilitators to be utilized for a comprehensive vaccine intervention in ob-gyn clinical settings. We conducted in-depth interviews with 24 providers, both healthcare providers (e.g., physicians, nurse practitioners, midwives) and practice managers, from urban and suburban ob-gyn practices in Georgia and Colorado about their immunization attitudes, practices, and patient experiences. Qualitative analyses included Pearson correlation tests to evaluate patterns and relationships within the data to determine themes. Six major themes emerged: 1) strong provider "buy in" for maternal immunization; 2) the supporting role of clinical/interpersonal cues for vaccine promotion; 3) varying provider-patient communication approaches and its influence on maternal and pediatric uptake; 4) an urgent need for a designated office immunization champion; 5) reimbursement and practice implementation challenges; and 6) region differences in attitudes and values toward maternal immunization. Although providers expressed strong support for maternal immunization practices and offered environmental cues for vaccine promotion, practices often lacked a designated, structured role for an immunization champion equipped to manage delicate conversations with patients. The findings reflect needs for immunization champion identification, training, and support, along with best practices guidelines to improve coordination of vaccine promotion and delivery efforts in ob-gyn provider offices. Additionally, provider training on communication approaches to enhance acceptance and uptake of maternal vaccines is warranted.